Navigating Religious Difference in Spiritual Care - Schipani, Daniel S. (Religions, 2024)
During the last two decades there has been growing research on intercultural and, more recently, interreligious care in the face of increased, global pluralization. Representatives of various traditions are making substantial contributions beyond the pioneering work of Christian clinicians and theoreticians. This essay addresses one of the challenges and opportunities associated with multi-faith contexts: the methodological and clinical question of how spiritual caregivers can effectively engage significant difference in interreligious caregiving situations. Therefore, the twofold goal of the article is to understand and to foster competent practice by counselors, psychotherapists, chaplains, pastors and other spiritual caregivers. The body of the text describes and illustrates five strategies that caregivers can employ plus a review of seven categories of therapeutic interventions.